Pengaruh Kompensasi dan Pengembangan Pegawai terhadap Kinerja Pegawai dengan Kepuasan Kerja sebagai Variabel Intervening pada Dinas Kearsipan dan Perpustakaan Kota Padang - Riri Nur Alia; Marta Widian Sari; Selvi Zola Fenia (Journal Economic Excellence Ibnu Sina, 2024)
This research aims to examine how much influence compensation and employee development have on employee performance with job satisfaction as an intervening variable in Padang City Archives and Library Services. The data collection method is through surveys and distributing questionnaires, with a sample of 70 respondents. The analytical method used is structural equation modeling using smartpls. The research results showed that there was a significant influence of compensation on job satisfaction. There is a significant influence of employee development on job satisfaction. There is a significant influence of compensation on employee performance. There is a significant influence of employee development on employee performance. There is a significant influence of job satisfaction on employee performance. Job satisfaction mediates the effect of compensation on employee performance. Job satisfaction mediates the effect of employee development on employee performance.